Identification of natural compound garcinone E as a novel autophagic flux inhibitor with anticancer effect in nasopharyngeal carcinoma cells - Dan Wei; Luolin Wang; Shunmei Lei; Han Zhang; Caihua Dong; Yao Ke; Yuting Su; Xiaoying Chen; Lianping Xia; Xiaoyang Kong; Fuqiang Yin; Xia Liu (Taylor & Francis Group, 2023)
AbstractContext Current chemotherapeutic drugs cannot meet the treatment needs of patients with nasopharyngeal carcinoma (NPC), so urgent action is needed to discover novel chemotherapeutic agents. Our previous study revealed that garcinone E (GE) inhibited the proliferation and metastasis of NPC, suggesting that the compound might display promising anticancer activity.Objective To examine the mechanism underlying the anti-NPC activity of GE for the first time.Materials and methods For MTS assay, NPC cells were treated with 2.5-20 μmol/L GE or dimethyl sulfoxide for 24, 48, and 72 h. Colony formation capacity, cell cycle distribution, and in vivo xenograft experiment of GE were assessed. MDC staining, StubRFP-sensGFP-LC3 observation, LysoBrite Blue staining, and immunofluorescence examined the autophagy of NPC cells after GE exposure. Western blotting, RNA-sequencing, and RT-qPCR measured protein and mRNA levels.Results GE suppressed cell viability with an IC50 of 7.64, 8.83 and 4.65 μmol/L for HK1, HONE1 and S18 cells. GE inhibited colony formation and cell cycle, increased autophagosome number, and inhibited the autophagic flux partially by blocking lysosome-autophagosome fusion, and repressed S18 xenograft growth. GE dysregulated the expression of autophagy- and cell cycle-related proteins such as Beclin-1, SQSTM1/p62, LC3, CDKs, and Cyclins. Bioinformatics GO and KEGG pathway enrichment analysis of RNA-seq showed that autophagy was enriched in differentially expressed genes upon GE treatment.Discussion and conclusion GE acts as an autophagic flux inhibitor, which may have potential chemotherapeutic use for NPC treatment and may have an application in basic research to explore the mechanisms of autophagy.